Genome-wide analysis of left ventricular maximum wall thickness in the UK biobank cohort reveals a shared genetic background with hypertrophic cardiomyopathy - Aung, N; Lopes, LR; van Duijvenboden, S; Harper, AR; Goel, A; Grace, C; Ho, CY; Weintraub, WS; Kramer, CM; Neubauer, S; Watkins, H; Petersen, SE; et al. (American Heart Association, 2023)
Background: Left ventricular maximum wall thickness (LVMWT) is an important biomarker of left ventricular hypertrophy and provides diagnostic and prognostic information in hypertrophic cardiomyopathy (HCM). Limited information is available on the genetic determinants of LVMWT.